Enhancing Students’ Online Engagement Among Online Distance Learning Institutions’ Students in Malaysia. The Role of Digital Readiness as a Mediator - Zahir Osman; Liana Mohamad; Ratna Khuzaimah Mohamad (2021)
This study evaluates the relationships between e-learning attitude, digital readiness and online engagement among online distance learning students in ODL higher education institutions in Malaysia. The structural equation (SEM) technique was employed to assess the relationship between e-learning attitudes and the influence of digital readiness mediating online engagement. The model was developed based on the conceptual development and subsequently analysed by adopting Partial Least Square (PLS). A total of 307 students completed the online survey. Statistically, the data analysis outcomes have clearly shown that all four suggested hypotheses developed in this study are positive and significant. The results showed that e-learning attitudes influence digital readiness while e-learning attitude and digital readiness influence students’ online engagement. At the same time, digital readiness influences the relationship between e-learning attitudes and online engagement among students in Malaysia from higher institutions. As a result, to encourage students in higher education to engage in their online studies, this study is relevant to the higher education practice in developing their online courses. (Abstract by authors)